Town boy - Lat Dato' 1951- (MPH Group Publishing, 2014)
Malaysian teenager Mat makes a life-changing move from the quiet kampung where he was born to Ipoh, the rapidly industrializing nearby town. Living far from his rural roots at a boarding school, he discovers bustling streets, modern music, heady literature, budding romance, and through it all his growing passion for art. The companion novel to the critically acclaimed Kampung Boy, Town Boy offers more of Lat's delicious storytelling and enchanting pen-and-ink artwork. At once exotic and familiar, his cartoon world builds a bridge for readers into another world, another culture, and another time.